Development of Soft Power Strategies in Spain and China within the Framework of Structural Diplomacy - Font Haro, Cristina; Pastrana Huguet, Josep (Sinología hispánica. China Studies Review, 2024)
This article proposes the observation of the similarities in the application of the concept of Joseph Nye in the development of diplomatic strategies of Spain and China, establishing a time axis between both countries and using basic premises formulated by Stephan Keukeleire in his definition of structural diplomacy. The chronological parallels between the two countries lead us to observe similar achievements in their evolution and diplomatic involvement, with the ultimate goal of configuring the basic principles of international society with their vocation for long-term influence. Therefore, they became State actors that ensure the stability and multilateralism of the system based on the internal transformations that have been conducted since the 1980s.